Clinical Approach to Leukoencephalopathies - Renaud, Deborah L. (Seminars in Neurology, 2012)
Recent advances in biochemical and molecular genetics have led to the discovery of new leukoencephalopathies. Despite these advances, many patients with leukoencephalopathy remain undiagnosed. A systematic approach to the investigation of these patients is needed to select the most appropriate testing strategy. In this article, the author presents a clinical and magnetic resonance imaging (MRI) based approach to the evaluation of patients with leukoencephalopathy.
Keywords: leukoencephalopathy; magnetic resonance imaging